The Influence of Brand Trust Halal Certification and Product Variety on Repurchase Intentions for Frozen Halal Foods - Ribhi, Ahmad Aufar; Arifin, Samsul; Novandalina, Arini (JOURNAL OF ADVANCED STUDIES IN MANAGEMENT, 2024)
This investigation is driven by the phenomenon of Repurchase Intention, which is evidenced by the notable decrease in sales of Anka Frozen Jepara during the preceding months. A heightened repurchase intention signifies an elevated degree of customer satisfaction when contemplating the adoption of a product. This research endeavor seeks to examine the impact of Brand Trust, Halal Label, and Product Variation on the Repurchase Intention of halal frozen food offerings. The study employed a sample comprising 97 respondents, who were consumers of Anka Frozen Food Jepara, selected through a non-probability sampling method, specifically accidental sampling. This approach entails the selection of participants from the target population based on convenience or serendipity. The results indicate that Brand Trust and Product Variation exert a significant influence on Repurchase Intention. Conversely, the variable of Halal Label does not exhibit a significant effect on Repurchase Intention. Concurrently, Brand Trust, Halal Label, and Product Variation collectively exert an influence on Repurchase Intention. These findings offer valuable insights for enterprises to prioritize the cultivation of consumer trust and the provision of diverse product variations to bolster repurchase intentions, whereas the role of halal labeling may necessitate further exploration to elucidate its limited impact within this framework.